2021
DOI: 10.1371/journal.pone.0258124
|View full text |Cite
|
Sign up to set email alerts
|

Giant sulfur bacteria (Beggiatoaceae) from sediments underlying the Benguela upwelling system host diverse microbiomes

Abstract: Due to their lithotrophic metabolisms, morphological complexity and conspicuous appearance, members of the Beggiatoaceae have been extensively studied for more than 100 years. These bacteria are known to be primarily sulfur-oxidizing autotrophs that commonly occur in dense mats at redox interfaces. Their large size and the presence of a mucous sheath allows these cells to serve as sites of attachment for communities of other microorganisms. But little is known about their individual niche preferences and attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 193 publications
(213 reference statements)
1
5
0
Order By: Relevance
“…Marithioploca spp. have also been reported (Gallardo et al, 1998;Flood et al, 2021), but are probably not widely distributed, and no specimens were observed at the sites studied here or detected based on 16S-RNA (data not shown). During the fieldwork, the water mass on the inner shelf was dominated by ESACW that prevented anoxic conditions in the bottom waters (Zabel et al, 2019).…”
Section: Study Areasupporting
confidence: 50%
“…Marithioploca spp. have also been reported (Gallardo et al, 1998;Flood et al, 2021), but are probably not widely distributed, and no specimens were observed at the sites studied here or detected based on 16S-RNA (data not shown). During the fieldwork, the water mass on the inner shelf was dominated by ESACW that prevented anoxic conditions in the bottom waters (Zabel et al, 2019).…”
Section: Study Areasupporting
confidence: 50%
“…The SAR324 clade was described for the first time in the Sargasso Sea ( Wright et al, 1997 ). The distribution of this taxon is relevant in deep waters and oceans ( DeLong et al, 2006 ; Brown and Donachie, 2007 ; Ghiglione et al, 2012 ; Dick et al, 2013 ; Boeuf et al, 2021 ; Flood et al, 2021 ) and is a major component of low-oxygen environments, under dysoxic and suboxic conditions ( Boeuf et al, 2021 ). The SAR324 reports underline a high flexible metabolism and a chemoautotrophic regime ( Boeuf et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also recently discovered that Ca . Thiomargarita hosts a large number of host-specific epibionts [28]. Consideration of these microorganisms, in addition to Ca .…”
Section: Discussionmentioning
confidence: 99%
“…We also recently discovered that Ca. Thiomargarita hosts a large number of host-specific epibionts [28].…”
Section: Discussionmentioning
confidence: 99%